2016
DOI: 10.1016/j.jbiomech.2016.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strength of aneurysmatic and dissected human thoracic aortas at different shear loading modes

Abstract: Rupture of aneurysms and acute dissection of the thoracic aorta are life-threatening events which affect tens of thousands of people per year. The underlying mechanisms remain unclear and the aortic wall is known to lose its structural integrity, which in turn affects its mechanical response to the loading conditions. Hence, research on such aortic diseases is an important area in biomechanics. The present study investigates the mechanical properties of aneurysmatic and dissected human thoracic aortas via tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 26 publications
3
70
2
Order By: Relevance
“…Recently, we investigated the effect of residual stress on the critical pressure for dissection propagation in [13], which demonstrated that residual stress can elevate the critical pressure and thus lower the risk propagation. Gültekin et al [14] used a numerical phase-field approach and, after parameter fitting, found good agreement with experiments by Sommer et al [15] on shear-loading tests of both aneurysmatic and dissected human thoracic aortas that showed that the orthotropic media has significantly greater resistance to out-of-plane than to in-plane shear loading. Sommer et al also found that aortas with dissections had on average much less mechanical strength than aneurysmal specimens.…”
mentioning
confidence: 61%
“…Recently, we investigated the effect of residual stress on the critical pressure for dissection propagation in [13], which demonstrated that residual stress can elevate the critical pressure and thus lower the risk propagation. Gültekin et al [14] used a numerical phase-field approach and, after parameter fitting, found good agreement with experiments by Sommer et al [15] on shear-loading tests of both aneurysmatic and dissected human thoracic aortas that showed that the orthotropic media has significantly greater resistance to out-of-plane than to in-plane shear loading. Sommer et al also found that aortas with dissections had on average much less mechanical strength than aneurysmal specimens.…”
mentioning
confidence: 61%
“…For diseases such as aortic dissections much remains to be uncovered. In particular, we need to learn more about the mechanical properties and the embedded collagen fiber distribution, including that between aortic layers [58,72]. We need to better understand what actually triggers an aortic dissection and how to predict the propagation on the basis of a suitable fracture criterion.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…tear propagation and rupture) necessitate the use of more advanced fluid-structure interaction (FSI) approaches to simulate the flow in this complex aortic condition. FSI couples CFD simulations with finite element modelling (FE) of the aortic wall; however, this method is subject to significant and additional modelling assumptions regarding the mechanical properties of the vessel, which are patient-specific and not known for the case of AD [13]. In addition, FSI models are difficult to setup and demand significant computational effort to be resolved.…”
Section: Introductionmentioning
confidence: 99%